Tourism Development and Social Marketing: A Review (International Journal of Innovative Research in Engineering & Management, 2021)
The purpose of this article is to demonstrate how social  marketing contributes to the growth of sustainable tourism. This  is a critical review work that draws on a variety of sources in the  tourism environment and field of study. When a company sets  marketing objectives in the framework of traveler marketing, an  imbalance is created, which is known as tourism marketing  instabilities. Tourism marketing's major purpose, both  economically and socially, is to attract as many visitors as  possible, so enhancing the tourism economy's development and  the value tourists get. More employment will be created, public  infrastructure will be erected, income will grow, and the ecology  and culture of local communities will be preserved as a result of  tourist promotion. The majority of tourist activities, on the other  hand, are determined to be incompatible with the goals of total  tourism development or long-term tourism. The tourist industry,  the host communities, the government, as well as visitors should  all bear moral duty for the tourism sustainability of a location.  However, the majority of them have not made sufficient efforts  to regularly apply sustainable tourist development concepts. This  is where social marketing comes in to help promote sustainable  tourist concepts. Social marketing methods attempt to influence  behavior without gaining financial advantage for the company  that uses them. Campaigns using social marketing methods  highlight the advantages of changing one's behavior and offer  chances for people to evaluate and make conclusions about their  activities. It is critical to strike a balance between increasing  tourism and promoting tourist sustainability. Advertisement,  marketing, distribution, sales, and other methods may be used to  promote the area, while communication and education can be  used to promote tourist sustainability.
Keywords: Marketing Imbalance; Social Marketing; Sustainable Tourism; Tourism Development